Implementasi Kebijakan Pengembangan Pariwisata Pada Objek Wisata Alam Goa Akbar Di Kabupaten Tuban - Irdina Iffata Qottrunnada; Ananta Prathama (Jurnal Ilmu Sosial dan Ilmu Politik)
The Goa Akbar tourist site, managed by the Tuban Regency Government, holds significant potential as a key source of local revenue in the tourism sector due to its strategic location in the heart of Tuban city. However, its development policy implementation still shows deficiencies. This research aims to analyze the implementation of tourism development policies, specifically at the Goa Akbar tourist site in Tuban Regency. The research method employed is qualitative descriptive, using data collection through observation, interviews, and documentation. The policy implementation theory of Donald Van Metter and Carl Van Horn serves as the analytical framework. The research findings indicate that the overall implementation of tourism development policies at the Goa Akbar tourist site is not yet optimal. Goals and targets of the policy, such as increasing Regional Original Income (PAD), have not been fully achieved. Moreover, there are shortcomings in resource management, particularly in facilities and limited tourist attractions due to budget constraints. In terms of the social, economic, and political environment, there is a lack of community participation and financial support from other parties in the development of the Goa Akbar tourist site. Nevertheless, aspects related to the characteristics of implementing agencies, the attitude of implementers, and inter-organizational communication in the development of the Goa Akbar tourist site have been well implemented by the Tuban Regency Culture, Youth, and Sports and Tourism Office.